Peran Mahasiswa KKN dalam Meningkatkan Kesadaran Pendidikan Masyarakat untuk Menekankan Angka Putus Sekolah di Desa Nosari Barat, Kecamatan Bintan Timur, Kabupaten Bintan - M. Pemberdi Intasir; Anggi Octa Hendriawan; Gustia Andini; Said Muhamad Ahyar; Muhamad Aldo Wirawan; Nadia Ayu Putri Priyani; Delvina Dea Anisa; Damayanti Simangunsong; Syafiq Maulana; Daniesa Aryanti; Destri Mardina (CV. ITTC INDONESIA, 2025)
The Community Service Program (KKN) in Nosari Barat Village, East Bintan District, was initiated due to the high risk of school dropouts caused by the low learning interest among children and adolescents. Economic limitations, lack of awareness of the importance of education, and insufficient motivation from the environment were identified as major contributing factors. The program applied a participatory approach through socialization, interactive lectures, motivational video screenings, and group discussions with children, parents, and the community. The results revealed an increase in educational awareness, stronger motivation among children to continue schooling, and greater parental involvement in supporting learning. This program highlights the significant role of KKN students as agents of change in reducing dropout rates. In conclusion, educational socialization activities effectively foster community awareness and should be sustained to ensure long-term impact.